An epidemiological study of asthma and its risk factors in school going children in Bhavnagar city, Gujarat, India - Tundia, Mohnish N.; Thakrar, Dhara V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Asthma is a common disease worldwide with significant ethnic and regional variations. This study will provide evidence about the prevalence of asthma and will highlight level of problem in community. The objective of the study was to estimate prevalence of asthma and determine the presence of environmental risk factors among children with asthma. Methods: This study was conducted in school-going children of standard 5 to 8 in Bhavnagar city in 2015. Sample size was 1428. All schools of Bhavnagar city were listed and required number of schools were selected randomly and approached for consent. Study forms were filled up by personal interview and physical examination followed by house to house visits. Data entry and analysis were done using software Epi info 7. Chi square test was calculated. Multiple logistic regression was carried out by backward step-wise Likelihood Ratio (LR) method. Adjusted OR for significant variable was then calculated. Results: Total prevalence of asthma was 9% (129/1428). Out of these, 61.18% were female and 38.82% were male children. It was found 36.43% in age group of 11 years and 47.3% in children of lower socio economic class. The adjusted odds ratio for male gender was 0.631 and for smoking were 2.353. Conclusions: Female children are 1.58 times more likely to develop asthma than male children. Children whose family members smoke are 2.35 times more likely to develop asthma.